2020
DOI: 10.24017/covid.11
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Its Association with COVID-19: A Narrative Review

Abstract: The naturalness of severe acute respiratory syndrome coronavirus 2 infections (SARS-Cov-2) appears to impact the respiratory system and lungs, however, the etiology of many cases exhibited several various features of the disease. The Coronavirus disease 2019 (COVID-19) symptoms are not limited to the virus’s first definitions. This review gathered the contemporary information throughout PubMed, Scopus, and Science Direct databases regarding possible effects of the virus in generating reactive oxygen species an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 81 publications
(89 reference statements)
0
16
0
Order By: Relevance
“…Neutrophils, M1 macrophages and endothelial cells produce ROS especially through NADH/NADPH oxidase (NOX) activation (Mittal et al, 2014). An interesting hypothesis by Baqi et al (2020). highlights the possibility that the activation of Ca 2+ -sensitive Nox and ROS production can be further stimulated by Sars Cov 2 entry via angiotensin-converting enzyme 2 (ACE2) receptor, inducing the generation of angiotensin 1,7 from angiotensin II and the consequent opening of Ca 2+ channels (Baqi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophils, M1 macrophages and endothelial cells produce ROS especially through NADH/NADPH oxidase (NOX) activation (Mittal et al, 2014). An interesting hypothesis by Baqi et al (2020). highlights the possibility that the activation of Ca 2+ -sensitive Nox and ROS production can be further stimulated by Sars Cov 2 entry via angiotensin-converting enzyme 2 (ACE2) receptor, inducing the generation of angiotensin 1,7 from angiotensin II and the consequent opening of Ca 2+ channels (Baqi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting hypothesis by Baqi et al (2020). highlights the possibility that the activation of Ca 2+ -sensitive Nox and ROS production can be further stimulated by Sars Cov 2 entry via angiotensin-converting enzyme 2 (ACE2) receptor, inducing the generation of angiotensin 1,7 from angiotensin II and the consequent opening of Ca 2+ channels (Baqi et al, 2020). Covid19 could be also treated with anti-oxidants materials as complementary support to decrease inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…They are potential causes of severe lower respiratory tract infections, followed by pneumonia, which is generally associated with cytokine storm production, inflammation, cell death, and other pathophysiological processes involving redox imbalance or oxidative stress. 115 COVID-19 patients are at a higher risk of developing inflammatory responses associated with fatal respiratory distress. Although limited clinical data is available to establish a link between oxidative stress and viral infection due to SARS-CoV-2, many lines of evidence still suggested that overproduction of reactive oxygen species (ROS) and deprived antioxidant system play a significant role in the pathogenesis and severity of SARS-CoV-2 viral infection.…”
Section: Role Of Vitamin E In Covid-19 Antiviral Effects Of Vitamin E On Covid-19mentioning
confidence: 99%
“…Nowadays, the COVID-19 pandemic represents a massive world public health problem caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [ 150 ]. This disease is characterized by oxidative stress [ 151 ] and neuroinflammation [ 152 ] along with a higher risk to develop delirium and psychomotor agitation [ 153 ]. Among the second-generation antipsychotics, quetiapine, risperidone, and especially injectable aripiprazole have been proposed as alternative treatment choices for COVID-19 patients with delirium [ 153 , 154 ].…”
Section: Second-generation Antipsychotics: Can They Exert An Antiomentioning
confidence: 99%